The evolving economy : essays on the evolutionary approach to economics - Witt, Ulrich (Cheltenham ; Northampton, MA : Edward Elgar, 2003)
In this important collection of essays, Ulrich Witt illustrates how the evolutionary approach can reveal not only where change comes from, and how it happens, but also where it will lead.
Includes bibliographical references and index
aia 12/09/13
Loan
Keywords: Evolutionary economics